РОЛЬ ВЧИТЕЛЯ ЯК СУБ'ЄКТА ПЕДАГОГІЧНОЇ КУЛЬТУРИ (Педагогіка вищої та середньої школи, 2009)
The article it devoted to the research of the importance of creative legacy of modern teacher m the leaching process.